Signification Des Structures N-S Du Plateau Des Aït Maghlif (Region D’eç-Çour, Versant Meridional Du Massif Ancien Du Haut Atlas, Maroc) - Anas Emran; Fida Medina (European Scientific Journal, ESJ, 2016)
Structural study of the recent deformations of the Eç-çour area, located on the southern slope of the massif ancien of the High Atlas, has allowed us to obtain the following results: (1) In the Ait Maghlif plateau, on the northern border of the Siroua volcanic massif, the N-S structures that are bounded by the reverse Imini fault to the north and the left-lateral Tawyalt−Agandiy fault in the south, correspond to forced folds on reverse faults and related folds related to a NW-SE compression, some of which were former normal syndepositional faults that were active in Cretaceous times; an intermediate phase corresponding to a NNE-SSW compression which is thought to have triggered the Siroua volcanism; (2) along de South Atlas Fault, the recent tectonism is expressed by folding and faulting of several Quaternary alluvial fans, some of which bear reverse/dextral slickensides.